Design and Evaluation of Hybrid Drivetrain Damper Considering the Influence of Engine Misfire on Torsional Shock - Guogeng Zhang; Tao Liu; Lingran Xie; Pengcheng Huang; Weilin Zhang; Xiaoxiang Yu; Xiaowen Song (Shock and Vibration)
Engine misfire is an accidental failure mode in internal combustion vehicles that can lead to the malfunction of power transmission system components. However, previous studies on engine misfire have generally focused on the engine rather than the drivetrain. In this study, we established a simulation model of a hybrid drive system with multiple degrees of freedom to investigate the torsional shock characteristics of the engine under normal and engine misfire conditions. Factors such as the torsional stiffness, gear-pair meshing stiffness, and moments of inertia for the damper, generator, and drive motor were considered. The dual-mass flywheel (DMF) was subsequently applied in the drivetrain model, and its stiffness parameters were varied to optimize their effects on the torsional shock experienced by the power transmission system. According to the results, the first- and second-stage stiffnesses of the DMF were set as 5.1 and 15.0 Nm/deg, respectively. Finally, the performance of the designed DMF damper was evaluated through simulations and physical tests of the drivetrain. The engine at full load under normal and engine misfire conditions as well as under a steady-state load when generating power at the engine output was investigated. The simulation results indicated that the torsional shock on the power transmission system satisfied the design limit of 500 Nm with an angular acceleration below 500 rad/s2. The errors between the simulated and measured peak impact torques and resonance speeds under the misfire condition were approximately 15% and 5%, respectively.